Study protocol to investigate the efficacy of normalisation of Advance Care Planning (ACP) for people with chronic diseases in acute and community settings: a quasi-experimental design - Sarah Jeong; Tomiko Barrett; Se Ok Ohr; Peter Cleasby; Michael David; Sally Chan; Helen Fairlamb; Ryan Davey; Peter Saul (BMC Health Services Research, 2019)
Abstract Background Advanced care planning (ACP) is a process that involves thinking about what medical care one would like should individuals be seriously ill and cannot communicate decisions about treatment for themselves. The literature indicates that ACP leads to increased satisfaction from both patients and healthcare professionals. Despite the well-known benefits of ACP, it is still underutilised in Australia. Methods The aim of this study is to investigate the effects of normalising ACP in acute and community settings with the use of specially trained normalisation agents. This is a quasi-experimental study, involving 16 sites (8 intervention and 8 control) in two health districts in Australia. A minimum of total 288 participants will be recruited (144 intervention, 144 control). We will train four registered nurses as normalisation agents in the intervention sites, who will promote and facilitate ACP discussions with adult patients with chronic conditions in hospital and community settings. An audit of the prevalence of ACP and Advanced Care Directives (ACDs) will be conducted before and after the 6-month intervention period at the 16 sites to assess the effects of the ACP service delivered by these agents. We will also collect interview and survey data from patients and families who participate, and healthcare professionals who are involved in this service to capture their experiences with ACP. Discussion This study will potentially contribute to better patient outcomes with their health care services. Completion of ACDs will allow patients to express their wishes for care and receive the care that they wish for, as well as ease their family from the burden of making difficult decisions. The study will contribute to development of a new best practice model to normalise ACP that is sustainable and transferable in the processes of: 1) initiation of conversation; 2) discussion of important issues; 3) documentation of the wishes; 4) storage of the documented wishes; and 5) access and execution of the documented wishes. The study will generate new evidence on the challenges, strategies and benefits of normalising ACP into practice in acute and community settings. Trial registration This project has been approved by the Hunter New England Human Research Ethics Committee (Approval No. 17/12/13/4.16). It has also been retrospectively registered on 3 October 2018 with the Australian New Zealand Clinical Trials Registry (Trial ID: ACTRN12618001627246). This study will operate in accordance with the National Health and Medical Research Council’s National Statement on Ethical Conduct in Human Research (2007) and the CPMP/ICH Note for Guidance on Good Clinical Practice.